The Impact of Artificial Intelligence on Firm Performance: An Application of the Resource-Based View to e-Commerce Firms - Chen, Donghua; Esperança, José Paulo; Wang, Shaofeng (Frontiers in Psychology, 2022)
The application of artificial intelligence (AI) technology has evolved into an influential endeavor to improve firm performance, but only a little research considers the relationship among artificial intelligence capability (AIC), management, driven decision making, and firm performance. Based on the resource-based view and existing findings, this paper constructs a higher-order model of AIC and suggests a research model of e-commerce firm AIC and firm performance. We collected 394 valid questionnaires and conducted data analysis using partial least structural equation modeling (PLS-SEM). As a second-order variable, AIC was formed by three first-order variables: fundamental, skill, and preference. AIC indirectly affects firm performance through creativity, AIM, and AI-driven decision making (AIDDM). Firm creativity, AIM, and AIDDM are essential variables between AIC and firm performance. Innovation culture thoroughly moderates the relationship between firm creativity and AIDDM as well as the relationship between AIDDM and firm performance. Environmental dynamism entirely mediates the connection between AIM and AIDDM. Among the control variables, firm age negatively affects firm performance, and employee size does not. This study helps enterprises leverage AI to improve firm performance, achieve a competitive advantage, and contribute to theory and management practice.